Muting the voices of the protesters - Betina Mawokomayi; Bevelyn Dube (Communicare)
The study interrogated News24’s framing of the 2015 Malamulele service delivery protest in South Africa. The study sought to find out what frames were used, why they were chosen and with what effect. Twenty newspaper articles published by News24 on the protest were purposively selected for inclusion in the study. The articles were analysed using quantitative and qualitative content analysis. Findings revealed that the reporters chose episodic frames which conformed with the protest paradigm and which depicted the protestors as violent, destructive, unreasonable and a threat to the economy of the local community and of the nation. The paper argues that the choice of sources and frames was largely informed by journalistic principles of news production and that this resulted in the voices of the protestors being stifled.